2021
DOI: 10.1007/s10608-021-10243-3
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress and Physical Health Symptoms in the Latinx Population During the COVID-19 Pandemic: Exploring the Role of Anxiety Sensitivity

Abstract: Objective The outbreak of the novel 2019 SARS2-Coronavirus disease (COVID-19) has led to substantial physical and mental health consequences. Rates of mortality and hospitalization are highest among those of racial and ethnic minority persons, including Latinx persons. Further, Latinx persons have been experiencing elevated mental health problems in response to the pandemic compared to non-Latinx Whites. The current study examined whether individual differences in anxiety sensitivity (AS) related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…Indeed, research from the COVID-19 pandemic shows that anxiety sensitivity is increased in adults and is positively associated with suicidal ideation (Allan et al, 2021), depression, and anxiety (Avidor et al, 2021). Taken together, these studies demonstrate that anxiety sensitivity could be a significant predictor of COVID-19-related fear and consequent safety behaviors (Mayorga et al, 2022). Thus, the primary aim of the present study was to assess the anxiety sensitivity of children and adolescents in northwest China early in the pandemic.…”
Section: Introductionmentioning
confidence: 80%
“…Indeed, research from the COVID-19 pandemic shows that anxiety sensitivity is increased in adults and is positively associated with suicidal ideation (Allan et al, 2021), depression, and anxiety (Avidor et al, 2021). Taken together, these studies demonstrate that anxiety sensitivity could be a significant predictor of COVID-19-related fear and consequent safety behaviors (Mayorga et al, 2022). Thus, the primary aim of the present study was to assess the anxiety sensitivity of children and adolescents in northwest China early in the pandemic.…”
Section: Introductionmentioning
confidence: 80%
“…Regarding physical health related to living with COVID-19 stressors, people who experienced job layoffs, financial strain, and difficulties transitioning to the lockdown period experienced poorer sleep health (Yuksel et al, 2021). Among Latinx people, those with higher anxiety sensitivity reported higher COVID-related stress and poorer general physical health (Mayorga et al, 2022). Physical activity is commonly considered an important way to maintain and promote good health.…”
Section: Covid-19 and Health Behaviorsmentioning
confidence: 99%
“…The findings were consistent for both samples wherein global anxiety sensitivity was related to the studied criterion variables and these effects were evident beyond the variance explained by age, sex, pre-existing medical conditions, and COVID-19 exposure (see Table 1 in the supplementary materials for lower-order relations with criterion variables). Among Latinx adults in the U.S., Mayorga, Garey, et al (2021) examined anxiety sensitivity during the pandemic among 188 adults. Here, in a cross-sectional examination, anxiety sensitivity was significantly related to the emotional impact of COVID-19 social distancing and economic adversity as well as physical heath symptom severity and fear of COVID-19; the effects were evident after adjusting for other theoretically and empirically relevant factors of gender, years living in the U.S., education, and work and home life COVID-19-related stressors.…”
Section: Narrative Reviewmentioning
confidence: 99%
“…Further, targeting and changing (improving) these constructs is related to better chronic illness outcomes in controlled research ( Leeuw et al, 2007 ). Some initial COVID-19 specific research has found evidence that certain interoceptive anxiety-related constructs, such as anxiety sensitivity, increase the risk for more severe physical health symptoms ( Mayorga, Garey, et al, 2021 ). However, more research is needed on the role of these transdiagnostic factors for better understanding pandemic related somatic symptoms, chronic illness, and course of COVID-19 infection, particularly among persons with mental health and addictive behavior problems.…”
Section: Section Four: Research Gaps Clinical Implications and Future...mentioning
confidence: 99%
See 1 more Smart Citation